SPDYing Up the Web. - Thomas, Bryce; Jurdak, Raja; Atkinson, Ian (Communications of the ACM, 2012)
The article discusses SPDY, a networking protocol that could replace HTTP (Hypertext Transfer Protocol), used for online data communication. It states that SPDY was developed by Internet corporation Google Inc. as a low-latency application-layer protocol. An analysis of similarities and differences between SPDY and HTTP is provided, covering topics such as request multiplexing, header compression, and server push. Other topics covered include security specifications, web browsers using SPDY, and the effects of SPDY on TCP (Transmission Control Protocol).